First record of Notopygos ornata (Grube, 1856) (Polychaeta: Amphinomidae) in continental Ecuador - Soledispa Macias, Jordy Armando (2023)
The polychaete Notopygos ornata (Grube, 1856) is recorded for the first time in continental Ecuador, the species is distributed from the Gulf of California to the Galapagos Islands. Its identification was based on specialized literature, taxonomic keys and original description. The main characteristic of this specie is its three-lobed caruncle, the complex pigmentation pattern that starts from chaetiger 7 in the dorsal region and the anus in a dorsal position in chaetiger 24. The present work confirms that its distribution extends on the Pacific side of the Ecuadorian continent, it is suggested to carry out more research on the polychaetofauna that exists in the country.